2021
DOI: 10.1055/a-1481-2733
|View full text |Cite
|
Sign up to set email alerts
|

Acquired FXIII Deficiency is Associated with High Morbidity

Abstract: Background: A factor XIII (FXIII) level >30% is considered necessary to prevent spontaneous bleeding. Bleeding is also a risk in patients with acquired FXIII deficiency, but the hemostatic level of FXIII in this context remains to be determined. Material & Methods: We retrospectively analyzed all patients diagnosed with acquired FXIII deficiency at a large hospital over 3 years (study ID NCT04416594, http://www.clinicaltrials.gov) and assessed clinical data to identify the best cut-off point for FXIII a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In other words, although patients in the FXIII group were initially prone to a much higher risk of death, the outcome of both groups was comparable in the end. This observation is supported by Duque et al who reported on the association between low FXIII activity and long ICU stay as well as high incidences of major bleedings [ 21 ].…”
Section: Discussionsupporting
confidence: 66%
“…In other words, although patients in the FXIII group were initially prone to a much higher risk of death, the outcome of both groups was comparable in the end. This observation is supported by Duque et al who reported on the association between low FXIII activity and long ICU stay as well as high incidences of major bleedings [ 21 ].…”
Section: Discussionsupporting
confidence: 66%
“…Thus, early bleeding control is essential for improving outcomes [ 24 ]. Duque et al recently demonstrated that an FXIII level <35% is associated with an increase in major bleeding events as well as prolonged ICU stays [ 25 ]. However, as the FXIII group lost more blood, both prior to and after FXIII administration (compared to non-substituted patients), it is unlikely that FXIII administration affected bleeding control.…”
Section: Discussionmentioning
confidence: 99%
“…However, defining the target population that might be at risk of acquired FXIII deficiency may be challenging. Based on our retrospective analysis [ 30 ], we have previously hypothesized that this high-risk population could be stratified per patient characteristics (being frail, plenty of co-morbidities, or oncological patients which would be at higher risk) and per procedural kinds (being emergent and/or major procedures that need intensive care unit admission and are linked to increased inflammatory response, the ones of higher risk).…”
Section: Importance Of Fxiii In the Acute Care Settingmentioning
confidence: 99%
“…Third, the level of FXIII activity required achieving effective hemostasis is to be determined, though we have recently reported it might has to be well above 30% in a mixed medical and surgical population [ 30 ], being then higher than in the inherited forms as previously suggested [ 13 ].…”
Section: Importance Of Fxiii In the Acute Care Settingmentioning
confidence: 99%
See 1 more Smart Citation